Mengabaikan Prinsip Kehati-hatian dalam Perizinan Lingkungan: Perbandingan Indonesia dengan Tiga Negara Lain dan Mekanisme Pembuktian Baru - Ajie Ramdan (Jurnal Penelitian Hukum De Jure, 2025)
Law Number 6 of 2023 concerning Job Creation revises Law Number 32 of 2009 by decriminalising Article 102 and merging it with Article 109. They have been changed from conduct offences to result-based offences. This study uses a normative legal research method combined with a comparative study using a statute research approach, which is used to analyse, explore, and review changes to Article 109. The findings of this study explain that because of revision of those articles, criminal sanctions cannot be imposed if someone or entities do not have environmental permits until environmental damage has already occurred. A study of the UK, the Netherlands, and Sweden shows those countries apply the precautionary principle by penalising the actions of entities that do not have environmental permits as conduct criminal offences. A comparison will be made between this and the environmental laws of Indonesia. Currently, to enforce Article 109 of Law Number 32 of 2009, prosecutors will need to employ the same proof method as that used for criminal offences as stipulated in Articles 98, 99, and 100. The novelty of this research is that the change from conduct offences to result-based offences have the potential to damage Indonesia’s environment. This will be scientifically proven in this article. The decriminalisation of Article 102 and the amendment of Article 109 of Law Number 32 of 2009 not only change the system of proof in cases of environmental permit violations, namely through scientific evidence, but also constitute a disregard for the precautionary principle.